ANALISIS FENOMENA SWING VOTERS PADA PEMILU REFORMASI DI KABUPATEN REMBANG - Susi Dian Rahayu (Journal of Politic and Government Studies, 2013)
AbstrackRembang regency is one area in Central Java. Rembang is one of area in CentralJava which has the most unique characteristics of the people regarding their politicalorientation. It can be explained where most people there have a tendency of pragmaticbehavior or tends to fluctuate in giving vote during the election. This can be seen from theresults of the results of elections to the election out of political parties different as thewinner. Legislative elections in 1999 won by PDI P, 2004 elections won by Golkar Party andthe 2009 election was won by the Democratic Party. If at the time of the legislative electionsin 2004 won by Golkar Party , while the contrarery result are shown on the presidential byplacing SBY-JK in the top spot, outpacing all her opponents. Whereas in the 2009 legislativeelections won by Democrats but for president instead won by Mega-Pro promoted by PDI-P.Seeing this just proves that many voters in the Rembang regency that are categorized asswing voters. The purpose of this study is to identify the factors that influence swing votersas well as the level of public trust in political institutions in the Rembang regency. Based onthis research, there are three factors that influence the swing voters in the Rembang regency.The first factor is a figure or personal candidates, secondly factor is mass mobilization, massmobilization is the most played is the mobilization of “kyai” and affiliated organizations, andthe last latter high rate of money politics in the election event. By choosing such a pattern ofbehavior can be concluded that the voters in the Rembang regency have flexible trust.Keywords: election, swing voters